Characteristic research on lithium iron phosphate battery of power type - Tseng Yen-Ming; Huang Hsi-Shan; Chen Li-Shan; Tsai Jsung-Ta (MATEC Web of Conferences, 2018)
In this paper, it is the research topic focus on the electrical characteristics analysis of lithium phosphate iron (LiFePO4) batteries pack of power type. LiFePO4 battery of power type has performance advantages such as high capacity, lower toxicity and pollution, operation at high temperature environment and many cycling times in charging and discharge and so on. The charging and discharging characteristics for LiFePO4 batteries of power type pack have been verified and discussed by the actual experiment. Base on the 12V10AH LiFePO4 battery was proceeding on charging and discharging test with over high current value and which investigate the parameters such as the internal resistance, the related charge and discharge characteristics of LiFePO4 battery pack, the actual value of internal voltage and internal resistance of the battery pack and by polynomial mathmatic model to approach the accury of inner resistance on discharging mode.